Awareness of COVID-19 Before and After Quarantine Based on Crowdsourced Data From Rabigh City, Saudi Arabia: A Cross-Sectional and Comparative Study - Aldhahri, Mai; Alghamdi, Rana (Frontiers in Public Health, 2021)
Background: Infection prevention and control measures are critical for the prevention of the spread of COVID-19. Aim: In this study, we aimed to measure and evaluate the level of awareness and knowledge of the prevention, symptoms and transmission control of COVID-19 before and after quarantine among the residents of Rabigh city and adjacent villages in Saudi Arabia. Methods: A cross-sectional online survey was conducted in two stages: the first stage took place before quarantine and the second stage took place after quarantine. The survey was filled out electronically. Results: A total of 448 participants responded and filled out the questionnaires. Females (73.70%) formed the largest number of participants for both stages. The majority of the participants were less than 30 years old (50.90%) and had a high education level in various sectors and levels (97.1%). It was noticeable that during the first stage, the participants’ awareness of COVID-19 symptoms was not very high: 13.62% did not know about the symptoms. However, by the second stage, awareness about symptoms had increased (9.6%). Conclusion: The residents of Rabigh city and the surrounding villages had good levels of knowledge about COVID-19.